Structure of the Escherichia coli response regulator NarL - Baikalov, I; Schröder, I; Kaczor-Grzeskowiak, M; Grzeskowiak, K; Gunsalus, R P; Dickerson, R E (Biochemistry (Easton), 1996)
The crystal structure analysis of the NarL protein provides a first look at interactions between receiver and effector domains of a full-length bacterial response regulator. The N-terminal receiver domain, with 131 amino acids, is folded into a 5-strand beta sheet flanked by 5 alpha helices, as seen in CheY and in the N-terminal domain of NTRC. The C-terminal DNA-binding domain, with 62 amino acids, is a compact bundle of 4 alpha helices, of which the middle 2 form a helix-turn-helix motif closely related to that of Drosophila paired protein and other H-T-H DNA-binding proteins. The 2 domains are connected by an alpha helix of 10 amino acids and a 13-residue flexible tether that is not visible and presumably disordered in the X-ray structure. In this unphosphorylated form of NarL, the C-terminal domain is turned against the receiver domain in a manner that would preclude DNA binding. Activation of NarL via phosphorylation of Asp59 must involve transfer of information to the interdomain interface and either rotation or displacement of the DNA-binding C-terminal domain. Docking of a B-DNA duplex against the isolated C-terminal domain in the manner observed in paired protein and other H-T-H proteins suggests a stereochemical basis for DNA sequence preference: T-R-C-C-Y (high affinity) or T-R-C-T-N (low affinity), which is close to the experimentally observed consensus sequence: T-A-C-Y-N. The NarL structure is a model for other members of the FixJ or LuxR family of bacterial transcriptional activators, and possibly to the more distant OmpR and NtrC families as well.